Subsurface Structure in Japan Based on P and S waves Travel Time Analysis Using Genetic Algorithm in Japan Seismological Network - A. M. Miftahul Huda; Bagus Jaya Santosa (International Journal of Science and Engineering, 2014)
Experiment to obtain the subsurface structure in Japan is conducted using seismograms analysis of earthquakes in Japan. All 101 data was used from events in 2012, selected by a maximum depth of 60 km and magnitude between 4.2 to 5.5 Mj. Determination of 1-D subsurface structure is done by utilizing the inversion method with genetic algorithm approach. P wave and S wave velocity structure are determined based on arrival times at receiver. The crustal thickness is known of 33,66 km. P wave velocity for the upper and lower crust, are 6,03 km/s and 6,92 km/s, respectively, and velocity in the upper mantle is 8,18 km/s. S wave velocity for the upper and lower crust are given 3,38 km/s and 3,89 km/s respectively, and the velocity in the upper mantle is 4,59 km/s. If the range integrated to the stable parameter of velocity structure, it shows stable result and the subsurface structure has sufficiently high compatibility.